2019
DOI: 10.18332/tid/114164
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new craving index for anticipating quitting smoking in patients who undergo the Japanese smoking cessation therapy

Abstract: INTRODUCTIONThe 10-item version of the Questionnaire of Smoking Urges (QSU-brief) has demonstrated excellent reliability. However, the QSU-brief may be too long to use in clinical settings. We developed a new craving index called the Tobacco Craving Index (TCI) and investigated how closely the TCI grade is associated with success of quitting smoking in Japanese smoking cessation therapy (SCT) patients.METHODSThe TCI questionnaire consists of two items: the first question asks about the strength of tobacco crav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…higher TCI grade was significantly associated with failure of quitting smoking after adjusting for gender, age, FTND, CES-D, type of prescription, motivation for quitting smoking, self-efficacy for quitting smoking and having a present illness. The present results together with our previous findings [11] demonstrated that TCI grading is an independent predictor for success of quitting smoking in smoking cessation settings. Therefore, we think that the TCI is a useful indicator for monitoring the efficacy of success of quitting smoking during smoking cessation treatment.…”
Section: Plos Onesupporting
confidence: 88%
See 3 more Smart Citations
“…higher TCI grade was significantly associated with failure of quitting smoking after adjusting for gender, age, FTND, CES-D, type of prescription, motivation for quitting smoking, self-efficacy for quitting smoking and having a present illness. The present results together with our previous findings [11] demonstrated that TCI grading is an independent predictor for success of quitting smoking in smoking cessation settings. Therefore, we think that the TCI is a useful indicator for monitoring the efficacy of success of quitting smoking during smoking cessation treatment.…”
Section: Plos Onesupporting
confidence: 88%
“…We previously examined how closely TCI grade is associated with success of quitting smoking among 85 individuals who received Japanese SCT compared with the QSU-brief (there was no overlap of participants in the previous study and the present study) [11]. The results suggested that the TCI, as well as QSU-brief, can be used as a predictive tool for success of quitting smoking.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…We aimed to recruit 84 participants, which would provide 90% power at an alpha level of .005 to detect an effect size of Cohen's d = 0.92, and 80% power at an alpha level of smoking cessation intervention consistently reported QSU-Brief scores that were ~10 points lower than those who failed to quit smoking (32).…”
Section: Participantsmentioning
confidence: 99%